Mastery Learning in Cognitive Computer Tutors - Gamache, Christopher Michael; Zhong, Billy; Maghfur, Anas B (Worcester Polytechnic Institute, 2009)
The ASSISTment is a cognitive computer tutoring system targeted towards middle school math students. Mastery learning was recently implemented into the system. This paper focuses on the effectiveness of mastery learning in the ASSISTment system. Results from a controlled experiment conducted in middle schools did not show significant results that mastery learning in the ASSISTment is effective. However, case studies of certain test subjects suggest that mastery learning could be effective for certain kinds of students. Hence, further work needs to be done on only certain kinds of students, particularly low achieving students. -